Evaluación del comportamiento de cuarzo mayor a 45 µm en crudo de cemento a granulometría variable, mediante difractometría rx y en base a evidencia empírica. - Fernández Vargas, Ana Gabriela (2014)
This research was conducted in the company Cementos Pacasmayo SAA in the Quality Control Division, during the period between the months January to March 2013, hence its purpose was to reduce the concentration of larger quartz 45 microns present in the crude. This required the development of the application of physical chemical raw quartz, then the contents of greater than 45 microns present in the raw variable quartz grain size was evaluated. This study is justified in that it has a theoretical value - practical behavior of quartz greater than 45 microns in crude, which allowed us to evaluate how feasible it was to continue grinding this without increasing production costs for energy expenditure milling. Furthermore, based on the physicochemical analyzes and empirical evidence. Methodologically the research work will be undertaken from sampling crude type I, until the determination of silica in quartzite variable grain crude by classical pathway analysis and X-ray With the results of determination of concentrations of quartz raw variable granulometry concluded that quartz is affected only for a season, and after this grinding had no significant effect.